Reassessment of potentially dangerous glacial lakes in Bhutan:(Acc: D 1742) - National Center for Hydrology and Meterology (Thimphu: National Center for Hydrology and Meterology, 2019)
Includes references.
Keywords: Glacial lakes in Bhutan